Determining the Absorbed Dose of Alpha Radiation due to Inhalation Radon Gas and Its Derivatives in Human Lung Using MCNPX 2.6.0 Simulation Model by Jafari et al. In Khorasan Razavi, Summer 2019 - Farhad Mohmmad Jafari; Javad Bahmani (Fasa University of Medical Sciences, 2021)
Background & Objective: People who work in closed and underground environments such as mines get radioactive gases into their respiratory system due to the concentration in the air. These radioactive substances, after entering the body's respiratory system, with radiating energetic particles, damage most of the live cells. The most damaged parts are in the alveolar air cells of the lung which may lead to cancer. Materials & Methods: The absorbed energy and annual effective dose due to the emitted alpha beam of radon and derivatives on alveolar air cells of the adult lung using MCNPX 2.6.0 simulation are determined. Color profiles are shown as a result of simulation of absorbed dose in the 27 alveoli of lung due to alpha radiation of radon and its derivatives. Results: The investigations show that polonium-210 (210Po), as one of the radon derivatives with long life, has the most annual effective absorbed dose in the human lung and as a result can cause the most damage to the living tissue of the alveolar air cells in comparison with the other radon derivatives. After this element, 218Po, 222Rn ,214Po and 214Bi have more the absorbed dose in the human lung, respectively. Conclusion: Most cancers from radon are generated by radon derivatives. They can play an important role in lung damage. Exposure to radon derivatives rises a person's lifetime risk of lung cancer. The risk increases in direct relationship with the length of exposure and the type of radon derivative. For reduction of 210Po is suggested the use of ventilation. It moves outdoor air into the building, and distributes the air within the building.